Fireflies. - Cheng, Natalie Xiaoyi. (2012)
This report documents the entire journey of my final year project development throughout the one and a half years. I will first give an overview of the project, elaborate on the obstacles that we have encountered as a team and how we dealt with them and the growth that took place throughout this one and a half year of production experience. I will also expound on how I have contributed to the project in various stages in the production pipeline. At the end of this report, I will touch on the work that I have done prior to the birth of this 150 seconds long animated short film, Fireflies.